An improved envelope spectrum via candidate fault frequency optimization-gram for bearing fault diagnosis. (14th April 2022) - Cheng, Yao; Wang, Shengbo; Chen, Bingyan; Mei, Guiming; Zhang, Weihua; Peng, Han; Tian, Guangrong
Highlights: Improved envelope spectrum via candidate fault frequencies (CFFs) Optimization-gram (IESCFFOgram) is proposed. IESCFFOgram determines the informative band of spectral coherence according to the identified CFFs. The merits of IESCFFOgram are verified by using simulated and experimental analysis. Abstract: Early fault identification of the rolling element bearings remains difficult because the repetitive transient signature generated via localized incipient damage is easily submerged by various interference components and strong noise. Spectral coherence (SCoh) is a breakthrough approach for revealing the second-order cyclostationary of bearing faults by displaying the energy flow of vibration signal jointly in a two-dimensional plane comprising the resonance frequency and bearing fault frequency. Considering the non-uniformity of fault information distribution in the whole spectral frequency band, the enhanced envelope spectrum (EES) obtained by integrating over the full spectral frequency band is vulnerable to strong background noise. Thus, how to identify an informative spectral frequency band for constructing a diagnostic improved envelope spectrum (IES) is crucial to accurately identify bearing faults. To address this issue, a feature-adaptive method called IES via Candidate Fault Frequency Optimization-gram (IESCFFOgram) is proposed to determine the informative spectral frequency band from SCoh for bearing fault diagnosis. The innovation of this method is to fully excavate the fault information hidden in the SCoh and adaptively determine the informative spectral frequency band according to the identified candidate fault frequencies. The proposed method is tested and validated on simulated signals, vibration datasets obtained from artificial fault bearing experiments, and accelerated bearing degradation tests. In addition, comparisons with state-of-the-art methods have been conducted to highlight the superiority of the proposed methodology.